Pembuatan Instrumen Asesmen HOTS untuk Meningkatkan Keterampilan Berpikir Kritis pada Model Problem Based Learning (PBL) Materi Pengukuran Fisika - Nurhikmah, Nurhikmah; Festiyed, Festiyed; Mufit, Fatni; Emiliannur, Emiliannur (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop an assessment instrument based on Higher Order Thinking Skills (HOTS) using the Problem Based Learning (PBL) model in physics measurement materials. The research method used is Research and Development (R&D) by adopting the Borg & Gall model. The research subjects consisted of three expert validators who assessed the validity of the instrument based on aspects of content, constructs, language, and additional rules. The data collection technique is carried out through instrument validation sheets filled in by experts. The data analysis technique uses the Aiken's V index to measure the level of validity of each instrument item. The validation results showed that the assessment instrument developed had an average value of Aiken's V index of 0.94 with a very valid category. Based on these results, this assessment instrument is feasible to be used effectively in physics learning to improve students' critical thinking skills.